1980
DOI: 10.1007/bf02245540
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod and fur lengths in the arctic fox (Alopex lagopus L.)

Abstract: :.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…The initial growth of the winter fur occurs in September, and continues until early December. The winter fur is 200% thicker than the summer fur [21]. The exact mechanism of the down regulation in Fig.…”
Section: Introductionmentioning
confidence: 94%
“…The initial growth of the winter fur occurs in September, and continues until early December. The winter fur is 200% thicker than the summer fur [21]. The exact mechanism of the down regulation in Fig.…”
Section: Introductionmentioning
confidence: 94%
“…It seems that the overall body surface of blue fox may be better insulated. Underwood & Reynolds (1980) found that those body sites which are exposed to environment, when the Arctic fox is in curled position, have greater fur lengths in all seasons than the more protected body sites. The importance of the ventral surface as an avenue of conductive heat loss was shown in our earlier paper (Korhonen et al, 1983a).…”
Section: Discussionmentioning
confidence: 91%
“…In the Arctic fox, fur length is nearly twice as long in winter as in summer. According to Underwood & Reynolds (1980) winter values of underfur on the back varies from 4 to 5 cm. These are consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations